Pain-related beliefs, coping and function: An observational study on the moderating influence of country of origin - Ferreira-Valente, A.; Sharma, S; Chan, J.; Bernardes, S. F.; Pais-Ribeiro, J.; Jensen, M. P. (Journal of Pain, 2023)
Chronic pain is a multidimensional experience and pain treatments targeting psychosocial factors reduce pain and improve function. These treatments often overlook the sociocultural factors that influence pain and the psychological factors associated with function in people with chronic pain. Although preliminary findings suggest that cultural background may influence pain and function via their effects on beliefs and coping, no previous study has directly tested if the country of origin moderates the associations between these psychological factors and pain and function. This study sought to address this knowledge gap. Five hundred sixty-one adults with chronic pain, born and living in the USA (n=273) or Portugal (n=288), completed measures of pain, function, pain-related beliefs, and coping. Between-country similarities were found in the endorsement of beliefs related to disability, pain control, and emotion, and in asking for assistance, task persistence, and coping self-statements responses. Portuguese participants reported greater endorsement of harm, medication, solicitude, and medical cure beliefs, more frequent use of relaxation and support seeking, and less frequent use of guarding, resting, and exercising/stretching. In both countries, disability and harm beliefs and guarding responses, were associated with worse outcomes; pain control and task persistence were associated with better outcomes. Six country-related small effect-size moderation effects emerged, such that task persistence and guarding are stronger predictors of pain and function in adults from the USA, but pain control, disability, emotion, and medication beliefs are more important in adults from Portugal. Some modifications may be needed when adapting multidisciplinary treatments from one country to another.